2015
DOI: 10.1590/0103-5150.028.004.ar01
|View full text |Cite
|
Sign up to set email alerts
|

Virtual and augmented reality technologies in Human Performance: a review

Abstract: Introduction : Today's society is influenced by Information and Communication Technologies. Toys that were once built by hand have been reinterpreted and have become highly commercialized products. In this context, games using Augmented Reality (AR) and Virtual Reality (VR) technologies are present in the everyday lives of children, youth and adults. Objective : To investigate how Physical Education professionals in Brazil have been making use of AR and VR games to benefit their work. Materials and methods : W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
1
0
5
Order By: Relevance
“…14 Essa tecnologia tem sido implantada no tratamento de diversas patologias neurológicas como a paralisia cerebral, as doenças degenerativas do sistema nervoso e a DP. 15 A relação inversa entre o risco de DP e exercício independe de intervalos etários específicos. 16 O presente estudo identificou que, após período de adaptação, não foram apresentadas dificuldades em executar atividades propostas, Ainda que padrão, a intervenção medicamentosa está associada ao desenvolvimento de complicações motoras típicas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…14 Essa tecnologia tem sido implantada no tratamento de diversas patologias neurológicas como a paralisia cerebral, as doenças degenerativas do sistema nervoso e a DP. 15 A relação inversa entre o risco de DP e exercício independe de intervalos etários específicos. 16 O presente estudo identificou que, após período de adaptação, não foram apresentadas dificuldades em executar atividades propostas, Ainda que padrão, a intervenção medicamentosa está associada ao desenvolvimento de complicações motoras típicas.…”
Section: Discussionunclassified
“…Atividade física configura-se como benéfica para a prevenção de inúmeras patologias e riscos associados. 15 O estudo em questão tende a contribuir para a melhora da estabilidade ortostática e da deambulação nesses pacientes em virtude dos objetivos dos jogos utilizados nesse protocolo.…”
Section: Discussionunclassified
“…Essa tecnologia da indústria do entretenimento pode ser utilizada como ferramenta de trabalho dos profissionais da saúde e da educação, jogos em RV são uma alternativa acessível, prazerosa, podendo promover o movimento do corpo todo e oferece vários níveis de dificuldade (LEVAC et al 2015). Outras vantagens como a diversão, que pode vir a remover a atenção das dores, além da promoção do abandono de uma vida sedentária, também são incentivos para aderir à essa prática (DA GAMA et al 2012;CROCETTA et al 2015).…”
Section: Referênciasunclassified
“…Serious-games in non-immersive virtual reality (VR), can incorporate a range of learning elements with interactive motor and cognitive challenges, in an engaging environment providing opportunity for individuals with neurological disorders to participate in repetitive, adaptive, meaningful, and challenging motor skill practice ( Gama et al, 2012 ; Levac et al, 2015 ; Lloréns et al, 2015 ; Schröder et al, 2019 ; de Moraes et al, 2020 ; Novak et al, 2020 ; Szturm et al, 2020 ). VR can motivate players to produce larger body movements and abandon a static position in front of the television or computer in order to play these interactive games ( Crocetta et al, 2015 ). Gross motor function ( Arnoni et al, 2019 ), motor performance ( Leal et al, 2020 ), gait performance, balance abilities, leg strength ( Cho et al, 2016 ) and reaction times ( Pourazar et al, 2018 ) have been shown to improve when VR technology is used in children with CP.…”
Section: Introductionmentioning
confidence: 99%